2011
DOI: 10.2131/jts.36.403
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorocarbon exposure, gender and thyroid function in the C8 Health Project

Abstract: Perfluorocarbons from common household products such as food containers, stain- resistant protection for clothing, furniture and carpets, paints, and fire-fighting foams are found in soil, water, plants, animal and human serum worldwide. Previous research has shown a significant association between these chemicals and thyroid disease in women. The present data from the C8 Health Project assessed thyroid function in a cross-sectional analysis of 52,296 adults with a year or more of exposure to perfluorooctanoat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
76
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 34 publications
9
76
1
Order By: Relevance
“…Weak associations between PFOA and PFOS exposure and reduced fertility in humans have been observed (Fei et al, 2009;Whitworth et al, 2012). A few human studies have also shown positive but weak associations between PFOA or PFOS exposure and preeclampsia, early menopause, delayed puberty onset, and semen quality, while other studies have shown no association with some of these reproductive parameters (Fei et al, 2009;Stein et al, 2009;Knox et al, 2011;Lopez-Espinosa et al 2011;Joensen et al 2009;Raymer et al 2012;Louis et al 2013). However, a recent prospective study shows an association between in utero exposure to PFOA and semen quality and reproductive hormones in male offspring 20 years later.…”
Section: Reproductive and Developmental Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Weak associations between PFOA and PFOS exposure and reduced fertility in humans have been observed (Fei et al, 2009;Whitworth et al, 2012). A few human studies have also shown positive but weak associations between PFOA or PFOS exposure and preeclampsia, early menopause, delayed puberty onset, and semen quality, while other studies have shown no association with some of these reproductive parameters (Fei et al, 2009;Stein et al, 2009;Knox et al, 2011;Lopez-Espinosa et al 2011;Joensen et al 2009;Raymer et al 2012;Louis et al 2013). However, a recent prospective study shows an association between in utero exposure to PFOA and semen quality and reproductive hormones in male offspring 20 years later.…”
Section: Reproductive and Developmental Toxicitymentioning
confidence: 99%
“…Some studies have reported effects of PFAS exposure on thyroid, liver, glucose and lipid metabolism. Although there are some inconsistencies between the studies, exposure to PFAS, especially PFOA and PFOS, overall seems to be associated with thyroid disease, although there also seems to be some differences concerning effects in men and women (Melzer et al, 2010;Knox et al 2011;Olsen et al, 1998;Olsen et al, 2003;Olsen et al, 2012;Gallo et al, 2012). Thyroid function regulates a wide array of metabolic parameters, such as lipoprotein metabolism, and thyroid dysfunction can thus have an important effect on lipid profile and may influence the overall risk for cardiovascular disease.…”
Section: Metabolism and Thyroid Functionmentioning
confidence: 99%
“…Endocrine disrupting effects of PFOA, including on steroid hormone production, have been reviewed [227]. Free serum thyroxine levels were not affected by PFOA/PFOS according to one report [296], while perturbations of thyroid function, with substantial gender differences were revealed in others [297,298]. Augmented free thyroxine serum levels were reported in adolescents and young adults, especially males, exposed to PFNA [299].…”
Section: More Exposed Populationsmentioning
confidence: 99%
“…The following associations have been seen for PFOA in the "C8 Health Project": increased total cholesterol and low-density lipoprotein in children and adolescents (Frisbee et al, 2010); increased blood lipid levels in relation to elevated PFOA (and PFOS) concentrations in the blood ; no associations to HDL cholesterol; positive associations with serum and liver enzymes (transaminase; a marker of hepatocellular damage) indicating hepatotoxic effect in humans (Gallo et al, 2012); positive association to serum uric acid (Steenland et al, 2010); no association between PFOA and TSH (n = 371) (Emmett et al, 2006); significant positive elevation in serum T4 and a significant reduction in T3 uptake in adults (Knox et al, 2011a); no associations with preterm birth and fetal growth restrictions (Savitz et al, 2012), positive association with hypothyroidism in children (Odds ratio (OR): 1.54; 95% confidence interval (CI): 1.00, 2.37) ; associations with Attention Deficit Hyperactivity Disorder (ADHD) in children 5-18 years of age, with a small increase in prevalence for the second quartile of exposure and a decrease for the highest versus lowest quartile (Stein and Savitz, 2011); more likely to have experienced menopause among perimenopausal women with higher level of PFOA (and PFOS), suggesting endocrine disrupting effects (Knox et al, 2011b); association with lower serum concentrations of IgA and IgE (for IgE in females only) (C8 Science Panel, 2009).…”
Section: Human Studies: Communities With High Exposed Populationmentioning
confidence: 99%